Colonial countryside : creative and historical responses / editors, Corinne Fowler, Jeremy Poynting. - Fowler, Corinne; Poynting, Jeremy (Peepal Tree Press, 2024)
This comissioned collection of short stories and poems, historical essays and art draws inspiration from National Trust properties whose owners engaged in the slavery business, in colonial administration or who were involved with the East India Company or British rule in India.